The Use of Statistical Parametric Mapping (SPM96) as a Decision Aid in the Differential Diagnosis of Dementia Using 99mTc-HMPAO SPECT - A. Barnes; D. Lusman; J. Patterson; D. Brown; D. Wyper (Behavioural Neurology)
In this study standard patterns of cerebral perfusion based on classifications described in the literature have been chosen and the ability of experienced imaging specialists to categorise the 99mTc HMPAO SPECT scans of patients referred to the department for investigation of dementia has been compared before and after the calculation of Statistical Parametric Maps (SPM—Wellcome Dept of Cognitive Neurology). The primary aim was to investigate whether SPM is an effective decision aid and whether it impacts on the confidence of image reporting. The secondary aim was to examine the influence of SPM on the agreement between image reporting and clinical diagnosis. The results showed that there was a slight decrease in agreement between the imaging specialists after the introduction of additional information from SPM (K = 0.57 to K = 0.5) and that agreement between imaging reporting (including information from SPM) and clinical diagnosis was moderate (K = 0.28). This study was able to confirm that SPM is capable of producing meaningful significance maps of individual patients in a routine clinical environment. However, there was no overwhelming evidence that SPM was able to resolve many of the dilemmas associated with the use of SPECT for the differential diagnosis of dementia. In particular, interpretation of SPECT perfusion patterns in dementia is a bigger problem than the initial identification of abnormalities.